School Environmental Influences, Student Discipline and Learning Motivation Toward Increasing Senior High Students Achievement - Pierre Senjaya, Fredson Kotamena, Freddy Ong, Carter Bing Andika, Agus Purwanto, Rudy Pramono (International Journal of Advanced Science and Technology, 2020)
The purpose of this research is to analyze school environmental influences, student discipline, and learning motivation towards learning achievement on a subject learning. This research is meant to student grade XI and XII. The research method is based on a survey with correlational technic analysis. It requires 100 students from grade XI and XII.This research shows that there are positive relationships and significant among variable. School environment variables with student achievement has a positive relationship; variable student discipline and motivation are also having a positive effect on student achievement results. The positive results of the correlation of all variables with student achievement, student motivation showed that most influence on student achievement. Motivation of students in a powerful learning will affect the outcome of the learning process. It will requires the involvement of all stakeholders in the school environment for students to apply discipline consistently and provide a variety of motivation to students that are likely to improve student achievement results further.